Новые материалы по фауне моллюсков и мелких млекопитающих позднего плиоцена одесского куяльника - Топачевский, В.А.; Скорик, А.Ф.; Чепалыга, А.А. (Вестник зоологии, 1979)
Complex studies of small mammals (Insectivora, Lagomorpha, Rodentia) and mollusks of the Odessa Kujalnik Upper Pliocene resulted in a comparison of the synchronous to it sea and continental deposits of the North Biack Sea area as well as in the correlation of the latter with the Akchagyl-Apsheron rock masses of the Caspian Sea. A complete coincidence is shown for the data of the paleomalacological and micropaleoterrioiogical studies within the stage and large intrastage, subdivisions within the stage of the marine and continental scales of Eastern Europe. However the remains of small mammals are more promising for distinguishing smaller time gradation at the given stage of knowledge.